The chronicle of Ibn al-Athir for the crusading period from al-Kamil fi’l-ta’rikh, part 3 : the years 589-629/1193-1231 the Ayyubids after Saladin and Mongol menace - Ibn al-Athir, Izz al-Din, 1160-1233 (Aldershot)
viii, 331 s.